Best practices for recruiting, retaining diverse adult students at community colleges. Issue 1 (18th August 2021) - Sutton, Halley
Abstract : A new report points out the disparity in earning a bachelor's degree between white Americans and Americans of color, and offers solutions for campuses looking to close equity gaps in degree attainment in higher education. The report, "Strategies for Improving Postsecondary Credential Attainment Among Black, Hispanic, and Native American Adults, " was produced by the Community College Research Center and the Lumina Foundation, and examines data from three different studies.